INFLUENCE OF THE PROJECT OF GYMNASTIC IN THE CLASSROOM ON THE FOCUS AND POSTURAL DISCOMFORT OF STUDENTS OF THE SCHOOL OF BASIC EDUCATION EDUCAR-SE, IN SANTA CRUZ DO SUL – RS, BRAZIL. (Fiep Bulletin - online, 2012)
Private schools increasingly try to intensify the teaching/learning process, making the school environment essentialfor students learning especially if they feel comfortable on their chairs and desks. The goal of this research was to investigate theinfluence of the Project of Gymnastics in the Classroom on the focus and postural discomfort. The project involved 52 students of7th and 8th grades of the School of Basic Education Educar-se, in Santa Cruz do Sul – RS, and occurred during three months. Toinvestigate the focus of the students it was used the numerical grid test and subjectively by applying a questionnaire. Thediscomfort during classes was measured through the map of postural discomfort. The results of the survey showed that theproject provided an average increase of 22.28 % in the focus of student of the 8th grade. Similarly, for the students of the 7th gradethe increase was of 15.81 %. The data provides an overall average increase of focus of 19.04%. In postural discomfort there wasa significant decrease in discomfort of the upper back and hip. In contrast, in other areas such as head, thigh and ankle there wasa small decrease and in the areas of the neck, shoulder, lower back (lumbar), elbows and knees remained unchanged. Based onthese data it is possible to conclude that the project of gymnastics in the classroom, of the Educar-se School can increaseconsiderably the focus and attention of the students in class, through the minimization of the postural discomfort.
Keywords: Gymnastic; Focus; Postural Discomfort.